Vaccination of Lambs with Killed Vaccine from E. Coli O157:H7 to Induce Cellular Immune Responses against Challenge with Virulent Type - Ali Hussein Fadhil (Journal of Global Pharma Technology, 2018)
This study was aimed to estimate the immune responses of lambs immunized with heat-killed E. coli O157:H7 in two different doses to induce cellular immune responses against challenge with virulent type. Twenty lambs of both sexes were randomly divided into four equal groups (5 animals in each group).  Group A: were immunized subcutaneously with 2 ml of heat killed vaccine with a dose of 1X108 CFU/ml mixed with equal volume of adjuvant twice (primary and booster dose) at two week intervals. Group B- five lambs were immunized with a same manner of group A but with a vaccine containing 1X1010 CFU/ml with adjuvant. Group C- lambs were injected S/C with 2 ml of sterile PBS mixed with equal volume of adjuvant twice in two weeks. Group D – lambs were left without any treatment. Post immunization all lambs examined for clinical signs, Moreover serum at 0, 7,14 ,21 , 28, 42, 56, and 70 days for estimation of Interferon gamma (INF-Y) and IgG levels by ELISA test. Results  showed  increases in Interferon gamma (INF-Y) values significantly in the two immunized groups  at 7,14, 28, and 48 days (0.270± 0.0052, 0.0.310± 0.0076, 0.365± 0.007, 0.428± 0.0089,  0.263± 0.007 ,0.268± 0.005, 0.339± 0.0035 ,0.409 ±0. 0035 ,0.489± 0.003)  respectively, compared with control groups,  while  results revealed  that the interferon values in group B which immunized   with  dose 1×1010  CFU/ml  was significantly  increased  compared with  its value in  lambs immunization  with dose  1×108   CFU/ml  at days  14 as well as 28, and 42.Keywords: Killed vaccine, E. coli O157:H7, Interferon gamma (INF-Y), IgG.